2008
DOI: 10.1089/jpm.2008.0080
|View full text |Cite
|
Sign up to set email alerts
|

Partners in Care: Together for Kids: Florida's Model of Pediatric Palliative Care

Abstract: Florida's program is the first in the nation to provide government-subsidized pediatric palliative care from the point of diagnosis onwards. Lessons learned from Florida's experiences will help guide other states and health plans that desire to implement a similar model of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 9 publications
0
54
0
Order By: Relevance
“…[17][18][19][20] The IOF was developed to measure the impact of children's illnesses on families, but has also been used with families of children with life-threatening illnesses. 13,14 The scale includes 15 items assessing various aspects of family stress and strain in various settings. Response categories for individual items are ''strongly disagree,'' ''disagree,'' ''agree,'' and ''strongly agree.''…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] The IOF was developed to measure the impact of children's illnesses on families, but has also been used with families of children with life-threatening illnesses. 13,14 The scale includes 15 items assessing various aspects of family stress and strain in various settings. Response categories for individual items are ''strongly disagree,'' ''disagree,'' ''agree,'' and ''strongly agree.''…”
Section: Methodsmentioning
confidence: 99%
“…Florida created guidelines of diagnoses for admission and those were used to identify children eligible for this study. 14 The reader is referred to Knapp et al 14 for a list of diagnoses codes that are eligible for Florida's pediatric palliative care program. All of the children in our study were eligible for Medicaid.…”
Section: Samplementioning
confidence: 99%
“…15 Florida has published its experience with the demonstration program developed in 2005 and titled Partners in Care: Together for Kids (PIC:TFK). 16 In April 2006, the state of Massachusetts signed into law ''An Act Providing Access to Affordable, Quality, and Accountable Care.'' The Pediatric Palliative Care Program was established in Section 24K of Chapter 111 of the General Laws.…”
Section: Formation Of the Ppcnmentioning
confidence: 99%
“…In paediatric palliative care, there is a broad spectrum of lifelimiting conditions requiring palliative care at a certain point during the disease trajectory. For example, Knapp et al identified more than 70 potentially life-limiting diagnoses (ICD-9 codes; differentiation into decimals not counted) [6].…”
Section: Cartographers In An Uncharted Terrainmentioning
confidence: 99%